Relationships between structure and physical properties in SmNi(1-x)Co(x)O3 - Pérez Cacho, J. J. (2000)
The crystal structure of SmNi(1-x)Co(x)O3 perovskites, with 0 ≤ x ≤ 1, has been determined at room temperature by Rietveld analysis from X-ray powder diffraction data. Polycrystalline samples have been prepared using high temperature and high oxygen pressure treatment. Different structural parameters such as the bond lengths or the bond angles, have been compared to the Ni/Co ratio. They have also been correlated with the magnetic and electrical properties of the series. SmNi(1-x)Co(x)O3 are orthorhombic perovskites, space group Pbnm. The expected linear dependence in the oxygen-transition metal bondlengths, d(M-O), for a solid solution, which is often described by the Vergard's law, is modulated by slight structural changes. In the 0.3 ≤ x < 0.9 range, an anomalous increase in d(M-O) can be correlated to the ferromagnetic interactions shown by these samples at low temperatures. In addition, in the x ≤ 0.1 range, there is a decrease in the orthorhombic distortion of the crystal structure along the series which agrees with a composition-driven metal insulator transition at room temperature. These structural features point out the phase diagram proposed earlier for the SmNi(1-x)CO(x)O3 series.